The Sudden Death of a Child: Unveiling Nigerian Mothers’ Experiences of Grief - Owoyemi Raji, Ruqayat; Rais, Haniza; Sheikh Ahmad, Ismail (IIUM Journal of Educational Studies, 2025)
The sudden death of a child is one of the most devastating losses a mother can experience. This experience is often associated with shock, trauma, and grief. Mothers in Nigeria face a high prevalence of sudden child deaths. Hence, the aim of this phenomenological study was to explore the challenges and grief experiences of mothers following the sudden death of a child, using focus group discussions (FGD) as a platform for investigation. The researcher served as the group leader and interviewer, working with four women from the Ministry of Women Affairs in Nigeria. The participants were four bereaved mothers, married for at least five years, who had lost a child. They were purposively selected for the study through word-of-mouth communication and announcements posted on the Ministry of Women Affairs notice board. Thematic data analysis was used to identify patterns, meaning and themes in the FGD data, which was derived from discussion, observations, and the experiences shared by the participants. The analysis revealed four major themes in the bereaved mothers’ grief experiences, including managing the emotional pain of the loss, coping with the reality of the death, having poor support systems, and struggling to move forward after the loss. The implications on professional grief counselling and support are discussed to assist grieving mothers to cope better in times of grief.